The New illustrated science and invention encyclopedia. (Westport, CT : Stuttman, 1989)
Earlier ed. published under title: The Illustrated science and invention encyclopedia.
Includes glossary and indices.
Keywords: Science -- Dictionaries; Engineering -- Dictionaries